Stressed β-cells contribute to loss of peri-islet extracellular matrix in type 1 diabetes - Johansen, Chelsea G.; Lam, Kenedee; Farnsworth, Nikki L. (Frontiers in Endocrinology, 2025)
IntroductionType 1 diabetes (T1D) is characterized by the immune-mediated destruction of insulin-producing β-cells in pancreatic islets. The peri-islet extracellular matrix (ECM) is a complex protein barrier that is lost in T1D, in part due to infiltrating immune cells. The contribution of stressed β-cells to ECM degradation during T1D remains unclear. MethodsTo bridge this gap, we used 12–15-week-old NOD mice and pancreas sections from healthy, ≥2 autoantibody positive (Aab+), and recent onset T1D donors. We focused on MMP-3 due to its role in degrading type IV collagen (COL IV) in the peri-islet ECM.ResultsTreatment with proinflammatory cytokines or hyperglycemia increased MMP-3 gene expression and protein levels in mouse and human islets. In NOD pancreas sections, increased MMP-3 expression in β-cells correlates with loss of COL IV during insulitis and hyperglycemia; however, this was independent of insulitis score. We observed similar increases in MMP-3 and loss of COL IV in islets and exocrine tissue from Aab+ and recent onset T1D donors.ConclusionThese results suggest that stressed β-cells degrade the ECM during preclinical T1D, further weakening the peri-islet ECM barrier and facilitating islet infiltration and death. Inhibiting expression of MMP-3 may represent a novel treatment to prevent islet death in T1D.